Effectiveness of Toothpaste from Activated Charcoal as Teeth Whitening: A Systematic Literature Review - Aziz, Abdul; Adinda Ayesha; Eka Sevianti; Gabril Victory Makalalag; M Alvian Noordiansyah; M Panji Wicaksono; Shofa Khairunnisa; Nia Yuniarsih (HM Publisher, 2023)
Charcoal toothpaste is claimed to have the ability to whiten teeth by removing stains and plaque. The activated charcoal particles in the toothpaste are believed to be able to absorb pigments or substances that cause stains on the tooth surface, such as plaque buildup, food scraps, or colored drinks. This study aimed to carry out a systematic review regarding the exploration of the effectiveness of activated charcoal as teeth whitening. The literature search process was carried out on various databases (PubMed, Web of Sciences, EMBASE, Cochrane Libraries, and Google Scholar) regarding the effectiveness of toothpaste from activated charcoal as teeth whitening. This study follows the preferred reporting items for systematic reviews and meta-analysis (PRISMA) recommendations. The process by which activated charcoal adsorbs plaque and tooth stains involves its adsorption properties and extensive porous structure. Activated charcoal particles have a very large surface area with large pore structures. This surface area provides more area to interact with substances that cause plaque and stains on teeth. Activated charcoal has a high adsorption capacity.